Lewis base complexes of AlH3: Structural determination of monomeric and polymeric adducts by X-ray crystallography and DFT calculations - Humphries, Terry; Munroe, K.; Decken, A.; McGrady, G. (2013)
The AlH3 adducts of TMEDA (Me2NCH2CH 2NMe2), DIOX (O(CH2CH2) 2O), TEA (Et3N), BDMA (PhNMe2), and TMPDA (Me2NCH2CH2CH2NMe2) have each been characterised by single-crystal X-ray diffraction at low temperature, by 1H, 14N and 27Al NMR and FT-Raman and FT-IR spectroscopy, and by DFT calculations and elemental analysis. Hence, AlH 3·TMEDA and AlH3·DIOX are both shown to adopt a polymeric structure, with the bidentate ligand bridging two Al centres, each of which adopts a trigonal bipyramidal (TBP) arrangement with equatorial hydride moieties. The 1 : 2 adduct AlH3·2BDMA is monomeric but the geometry at the Al centre resembles closely that of the polymeric TMEDA and DIOX complexes. AlH3·TEA alone adopts a monomeric structure in which the Al centre is tetrahedrally coordinated by three hydride and one amine ligand. The Al-L bond distance of 2.0240(17) Å for AlH 3·TEA is the shortest of all the complexes in this study, and AlH3·TEA also possesses the shortest Al-H bonds. AlH 3·DIOX has the shortest Al-L bond distance of the polymeric species (2.107(14) Å) on account of the higher electronegativity of the oxygen donor. The structure of AlH3·TMEDA was determined at low temperature (monoclinic space group P21/c), and salient features are compared to the previous room temperature study, for which a highly disordered orthorhombic space group (P212121) was reported. The polymeric structures appear to be stabilised by a number of intermolecular interactions and unconventional hydrogen bonds; these are most pronounced for AlH3·DIOX, whose chains are connected by highly directional C-H?H-Al bonding with an H?H distance of 2.32(6) Å. © The Royal Society of Chemistry 2013.